Circadian control of lung inflammation in influenza infection - Shaon Sengupta (Nature Portfolio, 2019)
The circadian clock affects immune responses, but its role in influenza infection is not well understood. Here, Sengupta et al. show that time of infection and the circadian clock have no effect on lung virus titers, but affect inflammation, morbidity and mortality.